NIRS Footprint of Bio-Fertilizers from Hay Litter-Bags - Masoero Giorgio; Delmastro Marco; Cugnetto Alberto; Giovannetti Giusto; Nuti Marco (Journal of Agronomy Research, 2018)
The biofertilization of cropsusing microbial biota in the soil (MBS) is a modern practice that is used to sustain fertility. MBS agents can promote the yield and health of crops, by luxuriating in the shoot as well as in the root systems. Farmers devoted to systematic MBS fertilization are creating a “Symbiotic” (S) form of agriculture, which offers a greater advantage of resilience than Conventional (C) or organic farming. Since MBS is involved in organic matter degradation, hay-litter-bag probes can be used to reflect a global functionality of the active soil, in the short-medium term. It is here shown that the NIRS hay-litter-bag technique, intended not as mass decay but as a quality evolution of the hay probes, can be modelled as a valid footprint of S vs. C soils. A patented MBS was used in eight experiments in which litter-bags from an S treated thesis were compared with equivalent litter-bags from a non-inoculated C thesis. The chemical signature of the S vs. C in the litter-bag composition was a percentage decrease of sugars and fibres. A smart NIRS device was used to discriminate the origin of the S vs. C litter-bags and a sensitivity of 71% (P<0.0001) was obtained. External validations on 37 S farms showed that three NIRS models discriminated the true positive S spectra, with a sensitivity of 90% as single and 98% as compound probabilities The NIRS radiation of the hay-litter-bags confirmed the results of the S vs. C agriculture soil footprint. Moreover, the SCIO-NIR devices also made it possible to connect the S farms in a smart network.
Keywords: NIRS